2020
DOI: 10.1021/acs.nanolett.0c03182
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Commercial Masks and Respirators and Cotton Mask Insert Materials using SARS-CoV-2 Virion-Sized Particulates: Comparison of Ideal Aerosol Filtration Efficiency versus Fitted Filtration Efficiency

Abstract: Shortages in the availability of personal protective face masks during the COVID-19 pandemic required many to fabricate masks and filter inserts from available materials. While the base filtration efficiency of a material is of primary importance when a perfect seal is possible, ideal fit is not likely to be achieved by the average person preparing to enter a public space or even a healthcare worker without fit-testing before each shift. Our findings suggest that parameters including permeability and pliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
97
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 26 publications
4
97
1
Order By: Relevance
“…A recent study by Sickbert-Bennett et al (71) showed similar PPL results where they evaluated multiple brands of surgical and procedure face masks on one test subject, obtaining mean values of 3.5 and 1.6 respectively. Hill et al's (54) investigation also demonstrated that homemade face coverings provided as-worn filtration efficiencies of 15-40% (PPLs of 1.18 to 1.67). Given that disposable procedure masks and reusable cloth masks are, by simplest definition, a piece of material held in position over the nose and mouth, it may be stated reasonably confidently that a PPL of 2.0-2.5 is likely the upper level of performance that can be anticipated from basic designs of this nature.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A recent study by Sickbert-Bennett et al (71) showed similar PPL results where they evaluated multiple brands of surgical and procedure face masks on one test subject, obtaining mean values of 3.5 and 1.6 respectively. Hill et al's (54) investigation also demonstrated that homemade face coverings provided as-worn filtration efficiencies of 15-40% (PPLs of 1.18 to 1.67). Given that disposable procedure masks and reusable cloth masks are, by simplest definition, a piece of material held in position over the nose and mouth, it may be stated reasonably confidently that a PPL of 2.0-2.5 is likely the upper level of performance that can be anticipated from basic designs of this nature.…”
Section: Discussionmentioning
confidence: 94%
“…4-18 (65) to obtain a PF ≥100 prior to the total inward leakage test being conducted, ii) the design of a FFR provides for a more effective face seal, and iii) the electret filtering material has a much higher filtration efficiency. A recent study by Hill et al (54) showed that qualitatively fitting a KN95 and N95 FFR to a headform resulted in a FFR efficiency of only 0.40, but when the KN95 FFR was sealed to the headform with adhesive, the efficiency increased to 0.967.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations